Sistem Informasi Pembayaran Sekolah Pada SMK Widya Kutoarjo Berbasis Web - Faizatun Karomah; Ike Yunia Pasa; Hamid Muhammad Jumasa (Universitas Muhammadiyah Purworejo, 2020)
The school payment system at SMK Widya Kutoarjo is still handwritten. Data related to payments such as building management payments, uniform payments, book payments, and government assistance are kept in the form of files, making them less effective and efficient. The purpose of this study is to create a school payment information system, with the benefit of facilitating the process of managing school payment data and making it easier for parents to monitor student payment status. The school payment information system designed using Context Diagrams, Data Flow Diagrams (DFD), and Entity Relationship Diagrams (ERD) aim to help the payment process to be more effective in managing data.